The regulatory effects of arginine on ovary development in the Chinese mitten crab Eriocheir sinensis - Changle Qi; Jinping Li; Kaiqi Huang; Xiaodan Wang; Chuanjie Qin; Erchao Li; Jianguang Qin; Liqiao Chen (Aquaculture Reports, 2024)
This study aimed to investigate the effects of arginine (Arg) on the vitellogenesis and ovarian maturation of Chinese mitten crab. Six isonitrogenous and isolipidic diets (1.83, 2.52, 3.26, 3.96, 4.81 and 5.52 % Arg) were fed to adult female Chinese mitten crab (60.05 ± 4.33 g). The feeding period lasted for eleven weeks. The results showed that gonadosomatic index of crabs increased with increasing dietary Arg concentrations from 1.83 % to 2.52 % and significantly decreased from 2.52 % to 5.52 %. The quadratic regression analysis based on gonadosomatic index estimated that the optimal Arg requirement for adult female crabs was 2.60 %. Dietary supplementation with 2.52 % Arg significantly increased the crude protein concentration in the ovary. A dose of 2.52 % Arg significantly decreased the vitellogenesis-inhibiting hormone (VIH) content in the hemolymph. Arg (2.52 %) significantly upregulated the Vg and protein kinase A (PKA) gene expressions and increased the cyclic adenosine monophosphate (cAMP) concentration in the hepatopancreas. Moreover, dietary supplementation with 2.52 % Arg significantly decreased the cyclic guanosine monophosphate (cGMP) concentration and downregulated protein kinase G (PKG) and p38 mitogen-activated protein kinase (p38 MAPK) gene expression. Arg at 2.52 % significantly increased hemolymph Vg content and the gene expression of the vitellogenin receptor (VgR). In conclusion, Arg at 2.52 % improved vitellogenesis and ovarian maturation by reducing the VIH content and regulating Vg expression via the cGMP/cAMP pathway.